Opportunity to reduce paediatric asthma in New South Wales through nitrogen dioxide control - Ben Ewald; Luke Knibbs; Guy Marks (Elsevier, 2021)
Abstract Objective: The main sources of nitrogen dioxide (NO2), road vehicles and electricity generation, are currently in a period of technological change. We assessed the number of cases of childhood asthma in New South Wales that could be avoided by lowering exposure to NO2 by 25% from current levels. Methods: Health impact assessment calculations for each of the 128 local government areas were based on the population of children aged 2 to 14, the prevalence of asthma derived from the 2017 NSW health survey, NO2 exposure from a land‐use regression model using satellite data, and risk estimates derived from two meta‐analyses and one Australian study. Results: A 25% reduction in NO2 below current exposure would lead to between 2,597 and 12,286 fewer children with asthma in NSW. The wide range in these estimates reflects the variation in concentration‐response functions used. Conclusions: Even the lowest of these estimates would be a worthwhile reduction in this common childhood illness. Implications for public health: A 25% reduction in NO2 is ambitious, but it is achievable through improved vehicle exhaust standards, increasing electric vehicle numbers, and reform of the electricity sector. Current Australian ambient air quality standards for annual NO2 should be revised downwards.